Human migration from the Levant and Arabia into Yemen since Last Glacial Maximum - Andreas Henschel; Riyadh Saif-Ali; Molham Al-Habori; Syafiq Azman Kamarul; Luca Pagani; Cynthia Al Hageh; Emilio Porcu; Nassim Nicolas Taleb; Daniel Platt; Pierre Zalloua (Scientific Reports, 2024)
Abstract While a broad consensus about the first successful migration modern humans out of Africa seems established, the peopling of Arabia remains somewhat enigmatic. Identifying the ancestral populations that contributed to the gene pool of the current populations inhabiting Arabia and the impact of their contributions remains a challenging task. We investigate the genetic makeup of the current Yemeni population using 46 whole genomes and 169 genotype arrays derived from Yemeni individuals from all geographic regions across Yemen and 351 genotype arrays derived from neighboring populations providing regional context. Principal Component Analysis shows stratification between Yemen districts but also with respect to nearby populations: Yemeni, other Arabian and Bedouin samples form a continuum towards the populations of the Levant, whereas East Africa and India appear strongly differentiated. This finding is further supported by higher Principal Components, admixture and haplogroup analyses, and F-statistics. Moreover, two-reference linkage disequilibrium decay estimates are most significant for Yemeni admixture from an ancient northern influx (up to 5220BP from Palestine) and East Africa (750BP). We show that the initial gene flow into the Yemeni populations of today came from the rest of Arabia and the Levant, and a less substantial and more recent genetic impact into coastal Yemen from East Africa, particularly.